2021
DOI: 10.3390/molecules26144258
|View full text |Cite
|
Sign up to set email alerts
|

VOCs Are Relevant Biomarkers of Elicitor-Induced Defences in Grapevine

Abstract: Grapevine is susceptible to fungal diseases generally controlled by numerous chemical fungicides. Elicitors of plant defence are a way of reducing the use of these chemicals, but still provide inconsistent efficiency. Easy-to-analyse markers of grapevine responses to elicitors are needed to determine the best conditions for their efficiency and position them in protection strategies. We previously reported that the elicitor sulphated laminarin induced the emission of volatile organic compounds (VOCs) by grapev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“… Yu et al (2020) elucidated metabolic profiles of 136 accessions of tea trees as part of a study on characterizing tea genetic resources in China. In a study on marker discovery, Lemaitre-Guillier et al (2021) demonstrated that the profiles of volatile organic compounds (VOCs) can be used as diagnostic markers for stress in grapevines.…”
Section: Application Of Metabolomics To Plant Breedingmentioning
confidence: 99%
“… Yu et al (2020) elucidated metabolic profiles of 136 accessions of tea trees as part of a study on characterizing tea genetic resources in China. In a study on marker discovery, Lemaitre-Guillier et al (2021) demonstrated that the profiles of volatile organic compounds (VOCs) can be used as diagnostic markers for stress in grapevines.…”
Section: Application Of Metabolomics To Plant Breedingmentioning
confidence: 99%
“…Among them are the well-studied stilbene phytoalexins associated with resistance to downy mildew and grey mould [17][18][19]. They are induced by various elicitors [6,8,12,15,20,21]. However, their analysis requires destructive sampling and is time-consuming because of several extraction and analysis steps.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have shown that elicitors can trigger VOC emission in plants [21,27,[31][32][33]. In greenhouse conditions, application of the elicitors, sulphated laminarin, chitosan (a chito-oligosaccharide (COS)) and Bastid ® , on grapevine plants increased the emission of mono-and sesquiterpenes [21,34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations